Using economic indicators in analysing financial markets - Krampen, Bernd (Emerald Publishing Limited, 2023)
Economic indicators provide invaluable insights into how different economies and financial markets are performing, enabling practitioners to adjust their investment strategies in order to gain knowledge about markets and to achieve higher returns. However, in order to make the right decisions, you must know how to interpret the relevant indicators. Using Economic Indicators in Analysing Financial Markets provides this important guidance. The first and second part of Using Economic Indicators in Analysing Financial Markets focuses on the short-term analysis, explaining exactly what the indicators are, why they are significant, where and when they are published, and how reliable they are. In the third part, author Bernd Krampen highlights medium and long-term economic trends: It is shown how some previously discussed and additional market indicators like stocks, bond yields, commodities can be employed as basis for forecasting both GDP growth and inflation. This includes the estimation of possible future recessions. In the fourth part the predominantly good forecast properties of sentiment indicators are illustrated examining the real estate market, which is rounded up by an introduction into psychology and Behavioural Finance providing further tips and tricks in analysing financial markets. Using Economic Indicators in Analysing Financial Markets is an invaluable resource for investors, strategists, policymakers, students, and private investors worldwide who want to understand the true meaning of the latest economic trends to make the best decisions for future profits on financial markets.